Chapter «Indietro non vogliamo tornare, indietro non sarà possibile tornare»: David Sassoli e António Costa perante os desafios europeus - Russo, Mariagrazia (Libere carte, 2023)
This article looks at the privileged relationship that David Sassoli had with Portugal at a time when the presidency of the European Parliament was shared with the presidency of the Council of Europe entrusted to António Costa. President Sassoli's speeches at the Social Summit held in the city of Porto on 7 and 8 May 2021 represent the synthesis of his socio-cultural and geopolitical vision. The Conference on the Future of Europe, which opened on 17 June 2021, ended when unfortunately Sassoli had already left us.